Предмет: Алгебра,
автор: Tanya5575
Решите уравнение: -х-7=4х+8
Выполните умножение: (2х-1)*(х+5)
Преобразуйте в многочлен: (3а-4)^2-9а^2
Помогите пожалуйста!
Ответы
Автор ответа:
1
-x-7=4x+8
-x-4x=8+7
-5x=15
x=15:(-5)
x=-3
-(-3)-7=4(-3)+8
Ответ:x=-3
(2x-1)(x+5)
2x²+10x-x-5
2x²+9x-5
(3a-4)²-9a²
9a²-24a+16-9a²
-24a+16
-x-4x=8+7
-5x=15
x=15:(-5)
x=-3
-(-3)-7=4(-3)+8
Ответ:x=-3
(2x-1)(x+5)
2x²+10x-x-5
2x²+9x-5
(3a-4)²-9a²
9a²-24a+16-9a²
-24a+16
Tanya5575:
Спасибоо большоое)
Похожие вопросы
Предмет: Информатика,
автор: pavlov7523
Предмет: Математика,
автор: puliakama8
Предмет: Химия,
автор: elizavetaogneva1993
Предмет: Математика,
автор: HotWheels
Предмет: Алгебра,
автор: faklak1